Intensive Care Unit Risk Assessment: A Systematic Review - Abbas HOMAUNI; Sanaz ZARGAR BALAYE JAME; Ebrahim HAZRATI; Nader MARKAZI-MOGHADDAM (Tehran University of Medical Sciences, 2020)
Background: It is of paramount importance to reduce the probability of clinical risks to improve the quality of health care services, make the relationship between service providers and patients more effective, enhance patient satisfaction, and decrease the rate of complaints regarding medical errors in hospitals. This study aimed at detecting potential and unacceptable risks occurring in the hospital ICUs. Methods: In this systematic review, all studies examining the risk assessment of ICUs in hospitals using Failure Mode and Effect Analysis method were reviewed. Google scholar, PubMed, Scopus, SID, Magiran and Web of Science databases were searched to find relevant articles published from 1980 to 2019. Results: The most frequent failures detected in the reviewed articles consisted of high risk of infection inwards for medical and nursing operations, high infection rates inwards for medical devices' operation within the unit, and early discharge. Moreover, the processes through which potential high-risk Failures were examined in these studies were injection or prescription process, suction process, the process of inserting or removing endotracheal tubes, the process of transferring patients from the operation room to the unit or vice versa, pressure ulcers, and processes related to the medical devices' operation. Conclusion: There are many possible reasons for failure occurring throughout these processes, and the failure modes occurring in these processes are more probable to cause serious damages to patients, have high repeatability with low probability of failure detection as the failures cannot be discovered by the personnel.